ChemInform Abstract: Silver‐Catalyzed Decarboxylative Alkynylation of Aliphatic Carboxylic Acids in Aqueous Solution. Issue 12 (14th March 2013) - Liu, Xuesong; Wang, Zhentao; Cheng, Xiaomin; Li, Chaozhong
Abstract The reactions proceed via an SET/radical pathway.